Association between apolipoprotein C-III levels and coronary calcification detected by intravascular ultrasound in patients who underwent percutaneous coronary intervention - Fukase, Tatsuya; Dohi, Tomotaka; Nishio, Ryota; Takeuchi, Mitsuhiro; Takahashi, Norihito; Chikata, Yuichi; Endo, Hirohisa; Doi, Shinichiro; Nishiyama, Hiroki; Okai, Iwao; Iwata, Hiroshi; Koga, Seiji; et al. (Frontiers in Cardiovascular Medicine, 2024)
There are few reports on the association between apolipoprotein C-III (ApoC-III) and coronary calcification using intravascular modalities. This study aimed to investigate the impacts of ApoC-III levels on coronary calcification using grayscale intravascular ultrasound (IVUS). Consecutive 263 culprit lesions for 202 patients who underwent percutaneous coronary intervention using grayscale IVUS were included in this study and divided into four groups based on quartile ApoC-III values. This study assessed plaque characteristics, including severe calcification (>180° arc) at the minimum lumen area site and presence of calcified nodules within the culprit lesion using grayscale IVUS, and evaluated whether ApoC-III levels were associated with coronary calcified plaques. The highest ApoC-III quartile [Quartile 4 (Q4)] had a higher proportion of complex lesions, calcified plaques, severe calcification, calcified nodules, plaque burden, and total atheroma volume than the lowest ApoC-III quartile [Quartile 1 (Q1)]. Additionally, multivariable logistic regression analysis showed that Q4 was significantly associated with severe calcification and calcified nodules, with Q1 as the reference (odds ratio [OR]: 2.70, 95% confidence intervals [CIs]: 1.04–7.00, p = 0.042; and OR: 3.72, 95% CIs 1.26–11.0, p = 0.017, respectively). Furthermore, ApoC-III level (1-mg/dl increase) was a strong significant predictor of severe calcification (OR: 1.07, 95% CIs: 1.00–1.15, p = 0.040) and calcified nodules (OR: 1.09, 95% CIs: 1.01–1.19, p = 0.034) according to the multivariable logistic regression analysis. This study is the first to verify that elevated ApoC-III levels are associated with the development of severe calcification and progression to calcified nodules as detected by grayscale IVUS.